Autocatalytic metal silicon powder as well as preparation method and application thereof

By using the preparation method of autocatalytic metal silicon powder in the Muller-Rochow process, the problems of low catalytic activity and conversion rate need to be improved are solved, and higher reaction activity and economic benefits are achieved.

CN119771419AActive Publication Date: 2025-04-08ZHEJIANG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411879772.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-08
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In the existing Muller-Rochow process, the three-component catalytic reaction system has low catalytic activity, large additive amount, silicon powder reaction rate and M2 monomer conversion rate need to be improved.

Method used

By using the preparation method of autocatalytic metal silicon powder, metal with autocatalytic ability is obtained by melting the silicon raw material into a silicon melt, and adding a main catalyst and additive metal under a protective atmosphere for mixing and melting. This method simplifies the reaction molecule process and turns it into a two-component solid-gas system, which improves the reaction activity and conversion rate.

Benefits of technology

The silicon powder reaction rate and M2 monomer conversion rate of the Muller-Rochow reaction are improved, the amount of catalyst is used and the frequency of additive adjustment during the reaction process is reduced, and the economic benefits of silicone production are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771419A_ABST
    Figure CN119771419A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemical raw materials, and particularly relates to autocatalytic metal silicon powder as well as a preparation method and application thereof. The method comprises the following steps: 1) smelting a silicon raw material into a silicon melt; (2) adding a main catalyst and auxiliary metal into the silicon melt, and mixing and smelting to obtain a mixed melt; and 3) quickly cooling and curing the mixed melt, and crushing to obtain the autocatalytic metal silicon powder. Through effective combination of silicon, the multi-element copper catalyst and the metal auxiliary agent, micron-scale contact of raw materials and the catalyst in Muller-Rochow reaction is converted into nano-scale contact, so that higher reaction activity and better M2 selectivity and silicon powder conversion rate are achieved, meanwhile, the use amount of the catalyst is reduced, and the production cost is reduced. And the real-time adjustment frequency of the auxiliary agent in the reaction process is reduced, so that the economic benefit of organic silicon production is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical raw materials, and in particular relates to autocatalytic metal silicon powder and a preparation method and application thereof. Background Art

[0002] The synthesis of organosilicon monomers is the basis for the production of various organosilicon polymers. At present, the synthesis of organosilicon monomers mainly adopts the Muller-Rochow process, and its process reaction mechanism is as follows: Figure 1 As shown. The key step of the Muller-Rochow process is the direct reaction of silicon with methyl chloride, which is usually carried out at high temperature in the presence of catalysts and additives. The products have diverse chemical structures and physical properties and are suitable for different industrial needs, among which the M2 monomer (Me2SiCl2) product has the greatest demand. Therefore, in addition to considering the highest possible productivity, that is, the highest silane output per unit time and reactor volume, this reaction also needs to consider the high selectivity of the target product dimethyldichlorosilane.

[0003] Over the past few decades, with the continuous progress of reactor design, catalyst improvement and deepening understanding of the reaction, the production efficiency and dimethyl selectivity in organosilicon synthesis have been continuously improved. However, due to the accumulation of impurities in metal silicon powder, oxidation, and the decrease in activity of catalysts and metal silicon after being wrapped by impurities, the reaction conversion rate (utilization rate) of metal silicon is low and the activity in the later stage of the reaction is poor. In particular, with the consumption and utilization of high-quality silicon materials, the impurity composition of the silicon materials used in recent years has become increasingly complex and increased, which has brought great troubles to organosilicon production.

[0004] In order to improve the selectivity of the Rochow reaction for M2 and the conversion rate of metallic silicon, we must start from the reaction process. Over the past few decades, catalysts have developed from metallic copper, cuprous chloride, ternary copper and composite catalysts, and have made important progress. However, its reaction process is still a complex solid (silicon powder)-solid (catalyst)-gas (methyl chloride) system. The continuous reaction requires the catalyst to adhere to the surface of the silicon powder and collide with the methyl chloride gas molecules before it can occur. This kinetic limitation is the fundamental bottleneck for improving the reaction activity and selectivity of the system.

[0005] However, at present, in the traditional three-component system, the contact, capture, adsorption and reaction between the catalyst and silicon powder require the help of the fluidized collision process, which is inefficient and not truly uniform. Therefore, the reaction activity can generally be promoted by increasing the specific surface area and reducing the particle size of silicon powder / catalyst. However, the fluidization process itself determines that the powder is difficult to be very fine, so as to prevent the powder from being carried away by the airflow; at the same time, the production of ultrafine metallic silicon and catalysts also requires additional power consumption, and the ultrafine powder is highly active, and the storage, transportation and operation are extremely difficult.

[0006] Considering the complex solid-solid-gas system of silicon powder-catalyst-chloromethane used in industry, the key to overcoming its kinetic limitations is to simplify the reaction molecular process, change the three-component solid-solid-gas system into a two-component solid-gas system, and compound the catalyst and metal silicon powder to obtain autocatalytic silicon powder. The composite autocatalytic metal silicon powder can continuously expose fresh copper-silicon active sites during the reaction, which are not related to the collision probability, so it can improve the reaction activity and the conversion of silicon powder.

[0007] It can be seen from this that simply mixing or kneading silicon and copper catalysts cannot directly and effectively improve the efficiency of the Rochow reaction and the conversion rate of the target product M2 monomer in practical applications, but requires further composite construction of the microstructure to ensure the effectiveness of the Si-Cu system catalyst. Summary of the invention

[0008] In order to solve the problems of low catalytic activity of the three-component catalytic reaction system used in the existing Muller-Rochow process, large amount of additives added, and the silicon powder reaction rate and M2 monomer conversion rate to be improved, the present invention provides a novel autocatalytic metal silicon powder, as well as a preparation method and application of the autocatalytic metal silicon powder.

[0009] The main purpose of the present invention is: 1. Construct a stable autocatalytic silicon powder with good reactivity; 2. Ensure that the autocatalytic silicon powder has good contact catalytic ability; 3. Ensure that the autocatalytic silicon powder has a good silicon powder reaction rate and M2 monomer conversion rate in the Muller-Rochow process.

[0010] To achieve the above objectives, the present invention adopts the following technical solutions.

[0011] A method for preparing autocatalytic metal silicon powder, The method comprises: 1) taking silicon raw material and melting it into silicon melt; The silicon raw material is metallurgical silicon, which is reduced, smelted, refined and impurity-removed to obtain silicon melt; After metallurgical silicon refining is completed, the oxygen content and impurity content in the silicon melt are reduced to a low level. At this time, adding catalyst metal under a protective atmosphere can better achieve precise control of its composition; 2) adding a main catalyst and an auxiliary metal into a silicon melt for mixed smelting to obtain a mixed melt; 3) The mixed melt is rapidly cooled and powdered to obtain autocatalytic metallic silicon powder.

[0012] Preferably, the main catalyst in step 2) is metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 10 to 80 wt%; Step 2) the auxiliary metal is zinc and / or tin and / or aluminum; When the auxiliary metal contains zinc, the amount of zinc added is 0.1 to 0.3 wt% of the silicon melt; When the auxiliary metal contains tin, the amount of tin added is 0.005 to 0.020 wt% of the silicon melt; When the auxiliary metal contains aluminum, the amount of aluminum added is 0.1 to 0.3 wt% of the silicon melt; The zinc and / or tin and / or aluminum in the auxiliary metal is added in the form of metal single substance and / or copper alloy.

[0013] As a preference, Step 2) The total amount of copper in the main catalyst and the auxiliary metal is 0.5-5.0wt% of the silicon melt.

[0014] As a preference, Step 2) The total amount of copper in the main catalyst and the auxiliary metal is 0.5-2.0wt% of the silicon melt; Step 2) The mass percentage of cuprous oxide in the main catalyst is 20-40wt%.

[0015] Preferably, in step 2), the mixed smelting process controls the smelting temperature to be 1600-1800° C. and the smelting time to be 5-10 min.

[0016] As a preference, In step 2), when adding the main catalyst and auxiliary metal to the silicon melt, metallic copper is first added for smelting, and then aluminum is added first according to the composition of the auxiliary metal, such as aluminum if present, and then zinc and tin are added for smelting, and finally cuprous oxide is added for mixed smelting.

[0017] As a preference, Step 3) the rapid cooling process controls the cooling rate to be ≥50°C / s; Step 3) The powder making adopts solidification crushing powder making and / or atomization powder making.

[0018] As a preference, Step 3) The milling process crushes the material to a mesh size of ≥80 meshes.

[0019] A self-catalytic metallic silicon powder.

[0020] Application of autocatalytic metal silicon powder, The autocatalytic silicon powder is used for catalytic synthesis of Me2SiCl2.

[0021] The present invention is a new catalytic system constructed based on the traditional Cu-Si catalytic system silicon powder. For example, in the preparation process of traditional self-catalytic silicon powder, the addition of auxiliary metal is usually not involved, and usually only additional ternary copper catalyst is added to improve its reaction activity, M2 selectivity and reaction efficiency. However, aluminum, phosphorus and other elements are removed as impurities through refining methods. In addition, it is necessary to add additional exogenous ternary copper catalyst powder during production or use.

[0022] However, such exogenous addition requires a long time of mixing in the reaction fluidized bed to ensure uniform mixing, which prolongs the start-up time of the reaction to a certain extent and causes the lag of the control in the middle and late stages of the reaction. The present invention firstly adopts a mixed smelting method to melt the required components and the silicon matrix together to form a whole, avoiding the effect of exogenous addition in the production and reaction process. The active sites exposed by the reaction process can continuously promote the occurrence of the reaction, thereby greatly improving the reaction activity and conversion rate of silicon powder.

[0023] In addition to the copper catalyst, the present invention additionally adds catalytic promoter metals such as zinc, tin, and aluminum. Since Cu itself is difficult to dissolve in silicon, and the melting points of the two are quite different, this causes Cu to easily segregate during the solidification process, forming a copper-rich segregation micro-region in the silicon matrix. Copper is added in a low amount as a catalyst, and copper segregation will cause most of the silicon to lose its autocatalytic activity. Therefore, the key to maintaining the catalytic activity and low addition of copper is to ensure its uniform distribution in the silicon matrix. From the perspective of alloy design, the addition of promoter metals can improve the stability of the Si-Cu system through multi-element eutectics and the complex intermediate phases formed on the basis of the Si-Cu system. Since Cu and Zn, Sn, and Al are similar elements, the segregation of copper can be suppressed to a certain extent after addition. In addition, elements such as Zn, Sn, and Al also promote the diffusion and activity of Cu ions during the reaction, which contributes to its more efficient free radical exchange ability.

[0024] The main reason for the above phenomenon is that there is a solid solubility limit of aluminum, zinc and tin in the Cu-Si system. The solid solubility limit of aluminum is relatively large. Generally speaking, the maximum amount of aluminum that can be directly used is about 4.2wt% of copper. However, both zinc and tin have extremely small solid solubility limits, both of which are only 0.7wt% of copper. The addition amounts of aluminum, zinc and tin in the auxiliary metals of the present invention are obviously more than this. For example, the amount of aluminum is about 2.0-60.0wt% of copper, and in a preferred range, the amount of aluminum is about 5.0-60.0wt% of copper, which obviously exceeds the solid solubility limit of aluminum. For example, the amount of zinc in the present invention is also about 2.0-60.0wt% of copper, and in a preferred range, the amount of zinc is about 5.0-60.0wt% of copper, which completely exceeds the solid solubility limit of zinc. Relatively good is tin. In the present invention, the amount of tin is about 0.1-4.0wt% of copper, and in a preferred range, the amount of tin is about 0.5-4.0wt% of copper, but it is obvious that there are also cases where it exceeds its solid solubility limit, and zinc and tin are in a competitive relationship, which is more likely to cause it to exceed its solid solubility limit. This will lead to segregation. However, if the amount added is insufficient, it will not effectively promote the diffusion of Cu ions and stimulate their activity, and the effect is weak.

[0025] In this regard, the present invention controls the order of adding the auxiliary metals and the cooling rate. When aluminum is added preferentially, the solid solubility limit of zinc and tin in the system can be increased to a certain extent, thereby inhibiting the precipitation of zinc and tin, especially having a significant inhibitory effect on the precipitation of zinc. At the same time, the present invention must provide a sufficient cooling rate to keep the melt in a state of homogeneous supersaturated solid solution and to keep the active catalytic metals in a uniform distribution state. In this way, it can be ensured that the three auxiliary metal elements of aluminum, zinc and tin can be evenly distributed to avoid segregation. On the other hand, the supersaturated solid solution can significantly improve the catalytic activity of silicon powder, because the supersaturated solid solution is in a high-energy state, which can provide more active sites and improve the catalytic activity. At the same time, the supersaturated solid solution usually has a more suitable band gap and a delocalized valence band top, which also has a significant improvement effect on contact catalysis.

[0026] It can be seen that the present invention forms a supersaturated solid solution by adding and regulating the auxiliary metal, which has an effective effect on improving the reaction activity, M2 selectivity and reaction efficiency of silicon powder.

[0027] The beneficial effects of the present invention are: The present invention effectively combines silicon and multi-copper catalysts with metal additives, so that the micron-level contact between the raw materials and the catalyst in the Muller-Rochow reaction is transformed into nano-level contact, thereby having higher reaction activity and better M2 selectivity and silicon powder conversion rate, while reducing the amount of catalyst used and the frequency of real-time adjustment of the additives during the reaction, thereby improving the economic benefits of organosilicon production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the reaction mechanism of the Muller-Rochow process; Figure 2 This is the microscopic element distribution diagram of the self-catalytic metal silicon powder prepared in Example 1; Figure 3 This is the microscopic element distribution diagram of the self-catalytic metal silicon powder prepared in Comparative Example 2; Figure 4 This is the microscopic element distribution diagram of the self-catalytic metal silicon powder prepared in Comparative Example 3. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0030] In the description of the present invention, it should be understood that the terms "thickness", "upper", "lower", "horizontal", "top", "bottom", "inner", "outer", "circumferential" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of the present invention, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined, and "several" means one or more.

[0031] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection, an electrical connection, or communication with each other; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0032] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0033] Example 1 A method for preparing autocatalytic metal silicon powder. The method comprises: 1) taking high-purity metallurgical silicon as a raw material, adding carbon with a mass ratio of about 3wt%, heating to 1600°C in a vacuum atmosphere for melting, and maintaining for 30 minutes for refining to obtain a silicon melt, wherein the oxygen content in the silicon melt is ≤60ppm, and the content of other inevitable impurities is ≤180ppm; 2) maintaining the melting temperature, adding the main catalyst and the auxiliary metal into the silicon melt in a vacuum atmosphere for mixed melting to obtain a mixed melt; The main catalyst is composed of metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 20wt%; The auxiliary metal is composed of copper-aluminum alloy, metal zinc and copper-tin alloy; During the addition process, the total amount of copper added is controlled to be 1.0wt% of the silicon melt, the amount of zinc added is controlled to be 0.2wt% of the silicon melt, the amount of tin added is controlled to be 0.01wt% of the silicon melt, and the amount of aluminum added is controlled to be 0.2wt% of the silicon melt; When adding the main catalyst and the auxiliary metal, first add the metal copper and continue to stir and melt for 2 minutes, then add the copper-aluminum alloy and continue to stir and melt for 2 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes to obtain a mixed melt; 3) The mixed melt is rapidly cooled and solidified at a cooling rate of 50°C / s, and then crushed by air jet mill through an 80-mesh sieve to obtain autocatalytic metal silicon powder.

[0034] The microscopic element distribution of the self-catalytic metal silicon powder obtained in this example was characterized. Figure 2 As shown, it can be seen that the silicon powder of the present invention does not segregate when excessive amounts of aluminum, zinc and tin are added, and the distribution uniformity of each element is high.

[0035] In addition, the performance of the self-catalytic silicon powder prepared in this example was verified and characterized, and it was directly used as a catalyst (i.e., a reaction contact) for the traditional Muller-Rochow process reaction. Before the reaction, the reaction system was first purged with N2 gas, and then switched to MeCl gas. After preheating, MeCl reacted with the contact contact. The product after the reaction flowed out from the lower end of the reactor, was condensed by a condenser, and was collected by toluene solution to obtain a test liquid. The tail gas was post-treated with alkaline solution, and the test liquid was quantitatively analyzed by gas chromatography after the volume was fixed. The product was characterized and calculated, and the selectivity of the M2 monomer (Me2SiCl2) and the silicon conversion rate were calculated respectively, and compared with the traditional silicon-ternary copper catalytic system (using an equal amount of catalyst, the catalyst is composed of silicon, ternary copper and zinc powder, and the mass ratio of silicon, ternary copper and zinc powder is Si:Cu / Cu 2 O / CuO:Zn=20:9.95:0.05) for comparison.

[0036] The characterization results are shown in the following table.

[0037] It can be clearly seen from the above characterization results that the self-catalytic silicon powder of the present invention has a very excellent catalytic effect, and is far superior to the existing silicon-ternary copper catalytic system in terms of M2 selectivity and silicon conversion rate, especially in terms of silicon conversion rate, the improvement is as high as more than 50%. This is mainly because in the traditional silicon-ternary copper catalytic system, the raw gas actually realizes the catalytic reaction under the joint action of contact silicon and ternary copper catalyst, so it is micron-level contact, the contact probability and contact area are relatively limited, and the directional conversion rate is also relatively low. However, under the action of the self-catalytic silicon powder of the present invention, the contact between the raw gas and the catalyst is nanometer-level contact, and the contact probability and contact area are greatly improved. At the same time, the addition of auxiliary metals also greatly improves the catalytic effect, efficiency and selectivity of the product M2. Under the joint action of the two, the actual silicon conversion rate has also produced an explosive improvement. At the same time, due to the effective combination of Si and ternary copper, the joint catalytic effect is enhanced, and the selectivity of M2 is also improved.

[0038] Example 2 Based on Example 1, only the total amount of copper in step 2) was changed (only by changing the amount of main catalyst metal copper and cuprous oxide) and the same performance characterization was performed on the obtained autocatalytic metal silicon powder. The characterization results are shown in the following table. Si:Cu mass ratio M2 Selectivity Silicon conversion rate Si:Cu mass ratio M2 Selectivity Silicon conversion rate 1:0.003 89.9% 46.3% 1:0.020 94.7% 51.3% 1:0.005 94.2% 50.2% 1:0.050 94.9% 49.6% 1:0.015 95.2% 50.8% 1:0.065 95.0% 43.1%

[0039] Through the above comparison, it can be found that when the Cu dosage is insufficient, the actual M2 selectivity is insufficient, and as the copper dosage gradually increases, the M2 selectivity increases and remains relatively stable in the experiment, but as the copper dosage increases, the silicon conversion rate shows a trend of first increasing and then decreasing. This is because when the copper dosage is too much, the actual carrier structure stability gradually decreases and the ability to adsorb raw gas is also weakened, resulting in the above situation. It can be seen that the mass ratio of Si and Cu should be controlled within an appropriate range to maintain the optimal catalytic effect.

[0040] Based on Example 1, only step 2 was changed to use different aluminum dosages (the silicon-aluminum alloy was replaced with equal amounts of metallic copper and metallic aluminum, and only the amount of metallic aluminum was adjusted) and the same performance characterization was performed on the obtained autocatalytic metallic silicon powder. The characterization results are shown in the following table. Si:Al mass ratio M2 Selectivity Silicon conversion rate Si:Cu mass ratio M2 Selectivity Silicon conversion rate 1:0.0005 83.9 32.7% 1:0.0025 94.5% 51.6% 1:0.0010 90.1 43.9% 1:0.0030 93.2% 49.2% 1:0.0015 95.0% 50.6% 1:0.0045 91.2% 39.1%

[0041] From the above comparison, it can be found that Al needs to be added in sufficient amount to produce a promoting effect. However, when the amount of aluminum is insufficient, it cannot effectively improve the reaction selectivity and reaction effect. When the amount of aluminum is too much, it will inevitably produce serious segregation, resulting in a direct decrease in reaction effect and conversion rate.

[0042] Similarly, based on the above-mentioned horizontal comparison test of aluminum, a comparison test of zinc and tin was also conducted. When the amount of zinc dropped to 0.05wt% of silicon melt, it had almost no improvement effect, and when the amount of zinc increased to 0.36wt% of silicon melt, segregation began to occur and gradually intensified. When the amount of zinc reached 0.50wt% of silicon melt, it produced negative optimization, that is, compared with the performance without adding zinc, the selectivity and reaction rate also decreased. The optimal amount of zinc was 0.1-0.3wt% of silicon melt. Similarly, when the tin content was only about 0.003wt% of silicon melt, there was almost no promotion and optimization effect, and when the tin content reached 0.022wt% of silicon melt, the selectivity and conversion rate dropped explosively, and the conversion rate dropped sharply to about 39.7%. The effective amount of tin was only 0.005-0.020wt% of silicon melt. This shows that the sensitivity of the system of the present invention to tin is relatively the highest, and the amount of tin should be most strictly controlled.

[0043] Example 3 A method for preparing autocatalytic metal silicon powder, The method comprises: 1) taking high-purity metallurgical silicon as a raw material, adding carbon with a mass ratio of about 3wt%, heating to 1600°C in a vacuum atmosphere for melting, and maintaining for 30 minutes for refining to obtain a silicon melt, wherein the oxygen content in the silicon melt is ≤60ppm, and the content of other inevitable impurities is ≤180ppm; 2) maintaining the melting temperature, adding the main catalyst and the auxiliary metal into the silicon melt in a vacuum atmosphere for mixed melting to obtain a mixed melt; The main catalyst is composed of metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 5 to 90 wt%; The auxiliary metal is composed of copper-aluminum alloy, metal zinc and copper-tin alloy; During the addition process, the total amount of copper added is controlled to be 1.0wt% of the silicon melt, the amount of zinc added is controlled to be 0.2wt% of the silicon melt, the amount of tin added is controlled to be 0.01wt% of the silicon melt, and the amount of aluminum added is controlled to be 0.2wt% of the silicon melt; When adding the main catalyst and the auxiliary metal, first add the metal copper and continue to stir and melt for 2 minutes, then add the copper-aluminum alloy and continue to stir and melt for 2 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes to obtain a mixed melt; 3) The mixed melt is rapidly cooled and solidified at a cooling rate of 50°C / s, and then crushed by air jet mill through an 80-mesh sieve to obtain autocatalytic metal silicon powder.

[0044] The performance of the self-catalytic silicon powder prepared in this example was verified and characterized. It was directly used as a catalyst (i.e., a reaction contact) in the traditional Muller-Rochow process reaction. Before the reaction, the reaction system was first purged with N2 gas and then switched to MeCl gas. After preheating, MeCl reacted with the contact. The product after the reaction flowed out from the lower end of the reactor, was condensed by a condenser and collected with a toluene solution to obtain a test liquid. The tail gas was post-treated with an alkaline solution. The test liquid was fixed to volume and then quantitatively analyzed by gas chromatography. The product was characterized and calculated. The selectivity of the M2 monomer (Me2SiCl2) and the silicon conversion rate were calculated respectively, and compared with the traditional silicon-ternary copper catalytic system (using an equal amount of catalyst, the catalyst is composed of silicon, ternary copper and zinc powder, and the mass ratio of silicon, ternary copper and zinc powder is Si:Cu / Cu2O / CuO:Zn=20:9.95:0.05).

[0045] The results of lateral comparison characterization by controlling the proportion of cuprous oxide in the main catalyst are shown in the following table.

[0046] From the above results, it can be seen that with the increase of cuprous oxide proportion, M2 selectivity shows a definite trend of first rising and then falling, especially in the early stage, the selectivity is significantly improved, but after further improvement, the selectivity decreases, while the silicon conversion rate basically maintains an upward trend. The direct reason for this is that the excessive addition of cuprous oxide affects its crystal structure, because as a catalyst, its crystal surface engineering has a significant effect on its catalytic performance, and the excessive addition of cuprous oxide leads to changes in the crystal surface structure, affecting the adsorption activity and catalytic activity. On the other hand, when the amount of cuprous oxide increases, it may lead to a large number of cuprous oxide crystals. Aggregation may affect the recombination of photogenerated electron pairs, thereby affecting the formation of electron-hole pairs. In the catalytic process, electron-hole pairs need to move to the crystal surface and contact with substances to react. If cuprous oxide crystals aggregate, it increases the difficulty of electron-hole pairs contacting with reactants, which may cause more electron-hole pairs to undergo impurity recombination before contacting with reactants, thereby affecting the catalytic efficiency. However, in terms of silicon conversion rate, excess cuprous oxide promotes silicon conversion by providing more comprehensive active sites. In the Cu-Si system, cuprous oxide may form specific interface active sites, such as Cu-SiO x The interface can promote the transformation of silicon, but the controllability of the transformation direction is weakened.

[0047] Therefore, for the present invention, the content ratio of cuprous oxide in the main catalyst should be controlled at 10-80wt%, especially at 20-70wt% to achieve the best effect.

[0048] Comparative Example 1 A method for preparing autocatalytic metal silicon powder. The method comprises: 1) taking high-purity metallurgical silicon as a raw material, adding carbon with a mass ratio of about 3wt%, heating to 1600°C in a vacuum atmosphere for melting, and maintaining for 30 minutes for refining to obtain a silicon melt, wherein the oxygen content in the silicon melt is ≤60ppm, and the content of other inevitable impurities is ≤180ppm; 2) maintaining the melting temperature, adding the main catalyst and the auxiliary metal into the silicon melt in a vacuum atmosphere for mixed melting to obtain a mixed melt; The main catalyst is composed of metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 20wt%; The auxiliary metal is composed of copper-aluminum alloy, metal zinc and copper-tin alloy; During the addition process, the total amount of copper added is controlled to be 1.0wt% of the silicon melt, the amount of zinc added is controlled to be 0.2wt% of the silicon melt, the amount of tin added is controlled to be 0.01wt% of the silicon melt, and the amount of aluminum added is controlled to be 0.2wt% of the silicon melt; When adding the main catalyst and the auxiliary metal, first add the metal copper and continue to stir and melt for 3 minutes, then add the copper-aluminum alloy and continue to stir and melt for 3 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 5 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 5 minutes to obtain a mixed melt; 3) The mixed melt is rapidly cooled and solidified at a cooling rate of 50°C / s, and then crushed by air jet mill through an 80-mesh sieve to obtain autocatalytic metal silicon powder.

[0049] The performance of the self-catalytic silicon powder prepared in this example was verified and characterized. It was directly used as a catalyst (i.e., a reaction contact) in the traditional Muller-Rochow process reaction. Before the reaction, the reaction system was first purged with N2 gas and then switched to MeCl gas. After preheating, MeCl reacted with the contact. The product after the reaction flowed out from the lower end of the reactor, was condensed by a condenser and collected with a toluene solution to obtain a test liquid. The tail gas was post-treated with an alkaline solution. The test liquid was fixed to volume and then quantitatively analyzed by gas chromatography. The product was characterized and calculated. The selectivity of the M2 monomer (Me2SiCl2) and the silicon conversion rate were calculated respectively, and compared with the traditional silicon-ternary copper catalytic system (using an equal amount of catalyst, the catalyst is composed of silicon, ternary copper and zinc powder, and the mass ratio of silicon, ternary copper and zinc powder is Si:Cu / Cu2O / CuO:Zn=20:9.95:0.05).

[0050] From the above characterization results, the M2 selectivity and silicon conversion rate of the self-catalytic metal silicon powder prepared in this example have significantly decreased. This is mainly due to the low actual melting point of each component in the auxiliary metal catalyst, which is very easy to burn out during the long mixed smelting process, resulting in a significant decrease in its optimization and improvement performance. Therefore, for the technical solution of the present invention, a sufficiently high smelting temperature, such as 1600-1800°C, and mixed smelting in a shorter time can ensure that it produces a relatively good smelting effect.

[0051] Comparative Example 2 A method for preparing autocatalytic metal silicon powder, The method comprises: 1) taking high-purity metallurgical silicon as a raw material, adding carbon with a mass ratio of about 3wt%, heating to 1600°C in a vacuum atmosphere for melting, and maintaining for 30 minutes for refining to obtain a silicon melt, wherein the oxygen content in the silicon melt is ≤60ppm, and the content of other inevitable impurities is ≤180ppm; 2) maintaining the melting temperature, adding the main catalyst and the auxiliary metal into the silicon melt in a vacuum atmosphere for mixed melting to obtain a mixed melt; The main catalyst is composed of metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 20wt%; The auxiliary metal is composed of copper-aluminum alloy, metal zinc and copper-tin alloy; During the addition process, the total amount of copper added is controlled to be 1.0wt% of the silicon melt, the amount of zinc added is controlled to be 0.2wt% of the silicon melt, the amount of tin added is controlled to be 0.01wt% of the silicon melt, and the amount of aluminum added is controlled to be 0.2wt% of the silicon melt; When adding the main catalyst and the auxiliary metal, first add the metal copper and continue to stir and melt for 2 minutes, then add the copper-aluminum alloy and continue to stir and melt for 2 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes to obtain a mixed melt; 3) The mixed melt is rapidly cooled and solidified at a cooling rate of 30°C / s, and then crushed by air jet mill through an 80-mesh sieve to obtain autocatalytic metal silicon powder.

[0052] The performance of the self-catalytic silicon powder prepared in this example was verified and characterized. It was directly used as a catalyst (i.e., a reaction contact) in the traditional Muller-Rochow process reaction. Before the reaction, the reaction system was first purged with N2 gas and then switched to MeCl gas. After preheating, MeCl reacted with the contact. The product after the reaction flowed out from the lower end of the reactor, was condensed by a condenser and collected with a toluene solution to obtain a test liquid. The tail gas was post-treated with an alkaline solution. The test liquid was fixed to volume and then quantitatively analyzed by gas chromatography. The product was characterized and calculated. The selectivity of the M2 monomer (Me2SiCl2) and the silicon conversion rate were calculated respectively, and compared with the traditional silicon-ternary copper catalytic system (using an equal amount of catalyst, the catalyst is composed of silicon, ternary copper and zinc powder, and the mass ratio of silicon, ternary copper and zinc powder is Si:Cu / Cu2O / CuO:Zn=20:9.95:0.05).

[0053] From the results of this example, compared with Example 1, this example uses a lower cooling rate, but the performance has a huge difference. Figure 3 As shown in the figure, after characterizing the microscopic element distribution, it can be clearly seen that elements such as tin and zinc have obvious segregation and enrichment, which indicates that a lower cooling rate cannot effectively and quickly achieve element fixation, and slow cooling will lead to component segregation and a decrease in comprehensive performance. This phenomenon will be further aggravated as the cooling rate decreases. However, a higher cooling rate will basically not cause a significant impact.

[0054] Example 4 A method for preparing autocatalytic metal silicon powder, The method comprises: 1) taking high-purity metallurgical silicon as a raw material, adding carbon with a mass ratio of about 3wt%, heating to 1600°C in a vacuum atmosphere for melting, and maintaining for 30 minutes for refining to obtain a silicon melt, wherein the oxygen content in the silicon melt is ≤60ppm, and the content of other inevitable impurities is ≤180ppm; 2) maintaining the melting temperature, adding the main catalyst and the auxiliary metal into the silicon melt in a vacuum atmosphere for mixed melting to obtain a mixed melt; The main catalyst is composed of metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 20wt%; The auxiliary metal is composed of copper-aluminum alloy, metal zinc and copper-tin alloy; During the addition process, the total amount of copper added is controlled to be 1.0wt% of the silicon melt, the amount of zinc added is controlled to be 0.2wt% of the silicon melt, the amount of tin added is controlled to be 0.01wt% of the silicon melt, and the amount of aluminum added is controlled to be 0.2wt% of the silicon melt; When adding the main catalyst and the auxiliary metal, first add the metal copper and continue to stir and melt for 2 minutes, then add the copper-aluminum alloy and continue to stir and melt for 2 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes, then add the metal zinc and the copper-tin alloy and continue to stir and melt for 3 minutes to obtain a mixed melt; 3) Atomization and powdering were performed under argon atmosphere to obtain autocatalytic metal silicon powder through an 80-mesh sieve.

[0055] The performance of the self-catalytic silicon powder prepared in this example was verified and characterized. It was directly used as a catalyst (i.e., a reaction contact) in the traditional Muller-Rochow process reaction. Before the reaction, the reaction system was first purged with N2 gas and then switched to MeCl gas. After preheating, MeCl reacted with the contact. The product after the reaction flowed out from the lower end of the reactor, was condensed by a condenser and collected with a toluene solution to obtain a test liquid. The tail gas was post-treated with an alkaline solution. The test liquid was fixed to volume and then quantitatively analyzed by gas chromatography. The product was characterized and calculated. The selectivity of the M2 monomer (Me2SiCl2) and the silicon conversion rate were calculated respectively, and compared with the traditional silicon-ternary copper catalytic system (using an equal amount of catalyst, the catalyst is composed of silicon, ternary copper and zinc powder, and the mass ratio of silicon, ternary copper and zinc powder is Si:Cu / Cu2O / CuO:Zn=20:9.95:0.05).

[0056] Judging from the above results, the use of atomization powder making process will not have a significant impact on the performance of the product. Because the cooling rate of atomization powder making usually reaches more than 1000℃ / s, it has an extremely high cooling rate. It also confirms the above view that for the technical solution of the present invention, it is necessary to ensure that the cooling rate is higher than a certain threshold. However, atomization powder making also needs to pay attention to the atmosphere. For example, the oxygen content of the environment must be lower than 200ppm, that is, a low-oxygen or even basically oxygen-free environment is constructed. At the same time, due to the particularity of the metal components of the auxiliary agent of the present invention, the use of conventional protective gas nitrogen will also have a significant impact on the results, resulting in severe nitridation of the product powder. If the argon atmosphere is replaced by a nitrogen atmosphere and the same atomization powder is carried out, the M2 selectivity of the product will decrease by about 13.8%, and the silicon conversion rate will drop to about 48.0%. It can be seen that the choice of atmosphere for atomization powder making is also particularly critical.

[0057] Comparative Example 3 A method for preparing autocatalytic metal silicon powder, The method comprises: 1) taking high-purity metallurgical silicon as a raw material, adding carbon with a mass ratio of about 3wt%, heating to 1600°C in a vacuum atmosphere for melting, and maintaining for 30 minutes for refining to obtain a silicon melt, wherein the oxygen content in the silicon melt is ≤60ppm, and the content of other inevitable impurities is ≤180ppm; 2) maintaining the melting temperature, adding the main catalyst and the auxiliary metal into the silicon melt in a vacuum atmosphere for mixed melting to obtain a mixed melt; The main catalyst is composed of metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 20wt%; The auxiliary metal is composed of copper-aluminum alloy, metal zinc and copper-tin alloy; During the addition process, the total amount of copper added is controlled to be 1.0wt% of the silicon melt, the amount of zinc added is controlled to be 0.2wt% of the silicon melt, the amount of tin added is controlled to be 0.01wt% of the silicon melt, and the amount of aluminum added is controlled to be 0.2wt% of the silicon melt; The main catalyst and the auxiliary metal are added simultaneously and smelted for 10 minutes under continuous stirring to obtain a mixed melt; 3) The mixed melt is rapidly cooled and solidified at a cooling rate of 50°C / s, and then crushed by air jet mill through an 80-mesh sieve to obtain autocatalytic metal silicon powder.

[0058] The performance of the self-catalytic silicon powder prepared in this example was verified and characterized. It was directly used as a catalyst (i.e., a reaction contact) in the traditional Muller-Rochow process reaction. Before the reaction, the reaction system was first purged with N2 gas and then switched to MeCl gas. After preheating, MeCl reacted with the contact. The product after the reaction flowed out from the lower end of the reactor, was condensed by a condenser and collected with a toluene solution to obtain a test liquid. The tail gas was post-treated with an alkaline solution. The test liquid was fixed to volume and then quantitatively analyzed by gas chromatography. The product was characterized and calculated. The selectivity of the M2 monomer (Me2SiCl2) and the silicon conversion rate were calculated respectively, and compared with the traditional silicon-ternary copper catalytic system (using an equal amount of catalyst, the catalyst is composed of silicon, ternary copper and zinc powder, and the mass ratio of silicon, ternary copper and zinc powder is Si:Cu / Cu2O / CuO:Zn=20:9.95:0.05).

[0059] The microscopic element distribution of the product in this example is also characterized. The characterization results are as follows Figure 4 As shown in the figure, from the results of this example, the main catalyst and auxiliary metal were added together during the mixed smelting process, which resulted in the inability of copper and aluminum to achieve initial distribution and coordination, and changed the overall smelting environment, making it difficult to form conditions that inhibit the precipitation of components such as zinc and tin. The uniformity of zinc and tin distribution decreased significantly, resulting in a large amount of segregation diffusion, and the performance of the final product decreased significantly. In addition, the above situation can also be verified after the microscopic element distribution characterization.

Claims

1. A method for preparing autocatalytic metal silicon powder, characterized in that: The method comprises: 1) Taking silicon raw materials and melting them into silicon melt; 2) adding a main catalyst and an auxiliary metal into the silicon melt for mixed smelting to obtain a mixed melt; 3) The mixed melt is rapidly cooled and powdered to obtain self-catalytic metallic silicon powder.

2. The method for preparing an autocatalytic metal silicon powder according to claim 1, characterized in that: Step 2) The main catalyst is metallic copper and cuprous oxide, wherein the mass proportion of cuprous oxide is 10-80 wt%; Step 2) the auxiliary metal is zinc and / or tin and / or aluminum; When the auxiliary metal contains zinc, the amount of zinc added is 0.1 to 0.3 wt% of the silicon melt; When the auxiliary metal contains tin, the amount of tin added is 0.005 to 0.020 wt% of the silicon melt; When the auxiliary metal contains aluminum, the amount of aluminum added is 0.1 to 0.3 wt% of the silicon melt; The zinc and / or tin and / or aluminum in the auxiliary metal is added in the form of metal single substance and / or copper alloy.

3. The method for preparing an autocatalytic metal silicon powder according to claim 1 or 2, characterized in that: Step 2) The total amount of copper in the main catalyst and the auxiliary metal is 0.5-5.0 wt% of the silicon melt.

4. The method for preparing an autocatalytic metal silicon powder according to claim 2, characterized in that: Step 2) The total amount of copper in the main catalyst and the auxiliary metal is 0.5-2.0 wt% of the silicon melt; Step 2) The mass proportion of cuprous oxide in the main catalyst is 20-40 wt%.

5. The method for preparing an autocatalytic metal silicon powder according to claim 2, characterized in that: Step 2) The mixed smelting process controls the smelting temperature to be 1600-1800°C and the smelting time to be 5-10 min.

6. The method for preparing an autocatalytic metal silicon powder according to claim 2 or 5, characterized in that: In step 2), when adding the main catalyst and auxiliary metal to the silicon melt, metallic copper is first added for smelting, and then aluminum is added first according to the composition of the auxiliary metal, such as aluminum, and then zinc and tin are added for smelting, and finally cuprous oxide is added for mixed smelting.

7. The method for preparing autocatalytic metal silicon powder according to claim 1, characterized in that: Step 3) the rapid cooling process controls the cooling rate to be ≥50°C / s; Step 3) The powder making adopts solidification crushing powder making and / or atomization powder making.

8. The method for preparing the autocatalytic metal silicon powder according to claim 1, characterized in that: Step 3) The milling process crushes the material to a mesh size of ≥80 mesh.

9. An autocatalytic metal silicon powder obtained by the method according to any one of claims 1 to 8.

10. An application of the autocatalytic metal silicon powder as claimed in claim 9, characterized in that: The autocatalytic silicon powder is used for catalytic synthesis of Me2SiCl2.

Citation Information

Patent Citations

  • Cooper base catalyst and preparation method thereof

    CN103316702A

  • Method for preparing ternary copper catalyst through vapor phase reduction of organic silicon waste contact body

    CN116212871A

  • Autocatalytic silicon powder as well as preparation method and application thereof

    CN118253302A

  • Preparation of organohalosilanes

    CN1834098A

  • Selective production of dimethyldichlorosilane

    US4684741A